2008
DOI: 10.1158/0008-5472.can-07-5203
|View full text |Cite
|
Sign up to set email alerts
|

The SV40 Large T Antigen-p53 Complexes Bind and Activate the Insulin-like Growth Factor-I Promoter Stimulating Cell Growth

Abstract: Inactivation of cellular p53 is a crucial step in carcinogenesis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 18 publications
2
60
0
1
Order By: Relevance
“…These observations suggest that SV40 large T plays an essential role in reprogramming sheep somatic cells. SV40 large T is an essential protein for SV40 DNA replication and disables the retinoblastoma and p53 tumor suppressor pathways [31][32][33][34]. It has been reported that knocking down p53 greatly increases reprogramming efficiency [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that SV40 large T plays an essential role in reprogramming sheep somatic cells. SV40 large T is an essential protein for SV40 DNA replication and disables the retinoblastoma and p53 tumor suppressor pathways [31][32][33][34]. It has been reported that knocking down p53 greatly increases reprogramming efficiency [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The literature also suggests that p53 stabilization may play a role in naturally occurring p53 gain-of-function mutants that exhibit an enhanced transformation potential (62), and it is tantalizing to think that LT might make use of a p53 gain-offunction in transformation (6,19,20). Thus, the interaction of LT with Bub1 might contribute to transformation both in an acute fashion via p53 stabilization and via a long-term effect on chromosome stability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in contrast to p53 target genes, possible LT target genes in cellular transformation cannot be detected by sequence homology of possible LT response elements. Recently, however, Bocchetta et al (6) demonstrated that the IGF1 gene is a direct transcriptional target of the LT-p53 complex, which positively regulates IGF1 transcription in SV40-transformed human mesothelial cells. Our analyses of Igf1 gene activity in SV40-transformed mouse fibroblasts contradict this result.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion that p53 in complex with SV40 LT might support SV40 phenotypic transformation has been received with due skepticism. However, recently it has been reported that human papillomavirus type 16 E6 protein mediated degradation of p53 in SV40-transformed human mesothelial cells induces a growth arrest by abrogating insulin-like growth factor 1 (IGF1) signaling (6). Those authors reported that LT and p53 associate with the IGF1 promoter within a multiprotein complex, in which p300 might be an important component required for IGF1 transcription.…”
mentioning
confidence: 99%